Evaluation of cell-penetrating peptide delivery of antisense oligonucleotides for therapeutic efficacy in spinal muscular atrophy - Hammond, S; Abendroth, F; Gait, M; Wood, M (Springer, 2019)
Antisense oligonucleotides (ASOs) are a widely used form of gene therapy, which is translatable to multiple disorders. A major obstacle for ASO efficacy is its bioavailability for in vivo and in vitro studies. To overcome this challenge we use cell-penetrating peptides (CPPs) for systemic delivery of ASOs. One of the most advanced clinical uses of ASOs is for the treatment of spinal muscular atrophy (SMA). In this chapter, we describe the techniques used for in vitro screening and analysing in vivo biodistribution of CPP-conjugated ASOs targeting the survival motor neuron 2, SMN2, the dose-dependent modifying gene for SMA.